The Effect of Turmeric Tamarind Drink on Menstrual Pain Reduction in Adolescent Girls at SMP Islam Indonesia - Siyami, Ana Soraya; Yuliani, Diah Atmarina; Muflihah, Ima Syamrotul; Achyar, Khamidah (Proceedings Series on Health & Medical Sciences, 2025)
Menstrual pain in adolescents daughter show sufficient prevalence tall. In European countries, dysmenorrhea happen around 45-97% of women, with prevalence lowest in Bulgaria (8.8%) and highest in Finland (94%). Menstrual pain happen Because excessive amounts of prostaglandins. Content curcumine and anthocyanins in turmeric sour capable reduce release prostaglandins so that can lower painful menstruation in teenagers daughter. This use type study quasy experimental use design nonequivalent ik group design. Population in study This that is all over teenager daughter at Belik Islam Middle School who experienced it painful menstruation totaling 51 with amount sample of 42 teenagers daughter taken using purposive sampling technique. Analysis bivariate using the paired sample t test. This show that happen decline painful menstruation in teenagers daughter where p value = 0.000. The result is p value 0.000 < 0.05 which means there is influence drink turmeric sour to decline painful menstruation in teenagers daughter. There is change scale painful before and after in the control group and group experiments and there are influence drink turmeric sour to decline painful menstruation in teenagers daughter at Belik Islam Middle School.